Komunikacja międzykulturowa w językach obcych a profil gospodarki na rynku światowym z punktu widzenia belgijskich przedsiębiorców - przedstawicieli kultury flamandzkiej - Verjans, Martine (Intercultural Communication in Foreign Languages and Successful Profiling on the World Market : the View of Belgian, I.C. Flemish Entrepreneurs, 2008)
Flanders' industrial image is changing rapidly. At first sight, the shift from standard production to low(er)-wage countries seems to be problematic. But it can also be considered a big challenge. It could give our Flemish, and certainly our Limburg companies the opportunity all the more to profile themselves on the world market, especially in the field of the conception of new high technological products adapted for the client, thanks to excellent knowledge centres. This should preferably happen in (European) "network connections". This does not only apply to the industry but certainly also to the services sector, as far as this strict difference still exists. In this context, efficient intercultural commu-nication and business negotiation in particular become even more important. To meet this end, a good knowledge of the business partner's culture and language is necessary, because culture is expressed directly in language and in the way of doing business. This article describes the importance of foreign intercultural communication for the Belgian and in particular the Flemish companies: to what extent are they confronted with the need of linguistic/ cultural knowledge? We also verity if the Flemish SME's have a strategy in the field of their foreign communication flows.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 17, s. 25-41